Power and Function in Labour Relations - Woods, H. D. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1960)
SummaryThe Author contends that the legal framework which has developed in Canada to deal with collective bargaining has been less favourable to the emergence of strong unions and effective collective bargaining than in the American case. This is explained better by fortuitous (and notably constitutional) circumstances than by calculated policy decisions. Canadian pragmatism in this field has led to a relatively massive State intervention which has strongly affected the basically unstable power relationship between labour and management. And the trend is increasing.